Peningkatan Efektifitas Program Pencegahan Anemia pada Ibu Hamil - Dian Isti Angraini; Fitria Saftarina; Efriyan Imantika; Novita Carolia (Jurnal Abdimas ADPI Sains dan Teknologi, 2023)
The programme to increase the effectiveness of the anemia prevention program in pregnant women is an effort to empower the community, namely health cadres to increase the scope of the program for giving iron tablets to pregnant women. Empowerment of health cadres through training and health education to increase the ability to persuade pregnant women to want and comply with taking blood-added tablets as recommended can help increase the scope of the program for giving blood-added tablets to pregnant women. The purpose of this programme is to train health cadres and health workers to carry out persuasive communication to pregnant women to want and obediently take blood-added tablets (empowered cadres). The method that will be used is persuasive communication training for health cadres through interactive lectures and discussions, video screenings and exercise simulations. This activity was carried out for 1 day and took place at the Panjang City Health Center in Bandar Lampung. The participants were 30 people who were health cadres, health workers and pregnant women. The results of the evaluation of the implementation of the programme found that there was an increase in participants' understanding as much as 90% became a good understanding, 10% of participants had a fairly good understanding, and none of the participants had a poor understanding of anemia in pregnancy, prevention of anemia in pregnancy, persuasive communication to pregnant women so willing and obedient in taking blood-added tablets. The average pretest result was 55.1 and an increase in the posttest result was 83.7. Based on the analysis using the Wilcoxon test, it was found that there was a statistically significant difference in the pretest and posttest scores of the service participants (p=0.000). This programme to increase the effectiveness of the anemia prevention program in pregnant women has proven to be effective.